Determinants of teachers’ attitudes toward inclusion of pupils with attention deficit hyperactivity disorder: The role of teacher education - Flavian, Heidi; Uziely, Eran (Frontiers in Education, 2022)
Given that teachers’ attitudes are an essential constituent of all academic and social processes taking place in their classrooms, the authors of the current study examined teachers’ attitudes and their sources specifically towards the inclusion of pupils with ADHD, taking into account demographic variables, teachers’ professionalism, and either a personal diagnosis of ADHD or prior acquaintance with it through relatives. The data, gathered from 475 participants’ responses to questionnaires, revealed that professional teacher training was only a secondary factor influencing attitudes regarding the inclusion of children with ADHD. A more prominent factor was teachers’ own diagnosis of ADHD or prior experience with children/relatives with ADHD. Study results are followed by practical suggestions for improving teacher education based on these findings.